Unsupported MoS2-Based Catalysts for Bio-Oil Hydrodeoxygenation: Recent Advances and Future Perspectives - Cao, Jing; Zhang, Youming; Wang, Li; Zhang, Cen; Zhou, Congshan (Frontiers in Chemistry, 2022)
In recent years, unsupported MoS2-based catalysts have been reported as promising candidates in the hydrodeoxygenation (HDO) of bio-oil. However, how to prepare MoS2-based catalysts with both high activity and good stability for HDO reaction is still challenging and of great importance. Hence, this mini-review is focused on the recent development of unsupported MoS2-based HDO catalysts from the understanding of catalyst design. Three aspects including morphology and defect engineering, metal doping and deactivation mechanism are highlighted on adjusting the HDO performance of MoS2-based catalysts. Finally, key challenges and future perspectives about how to design efficient catalysts are also summarized in the conclusions.